(untitled) (Eurasian Journal of Physics,Chemistry and Mathematics, 2022)
The article uses methods of mathematical modelling in the analysis of the socio-economic system. With the help of the Mathcad program, a multifactorial mathematical model was built for solving practical economic problems, which makes it possible to calculate the value of the production function and build multivariate regression models